2023
DOI: 10.3389/fimmu.2023.1023116
|View full text |Cite
|
Sign up to set email alerts
|

New methods for the quantification of mixed chimerism in transplantation

Abstract: BackgroundQuantification of chimerism showing the proportion of the donor in a recipient is essential for the follow-up of hematopoietic stem cell transplantation but can also be useful to document an immune tolerance situation after solid organ transplantation. Historically, chimerism has been quantified from genomic DNA, but with technological advances, chimerism from donor-derived cell-free DNA seems particularly relevant in solid organ transplantation.MethodsThe reference method was until recently the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Liacini et al [ 2 ] calculated the overall CV as 5.08% (ranging from 0% to 11.21% at the expected chimerism value of 0.1–10%), and Janakiraman et al [ 13 ] demonstrated within- and across-run variability of 4.7% and 4.1%, respectively. Additionally, Picard et al documented a lower LOQ (0.22%) than that reported by the manufacturer ( Table 5 ) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liacini et al [ 2 ] calculated the overall CV as 5.08% (ranging from 0% to 11.21% at the expected chimerism value of 0.1–10%), and Janakiraman et al [ 13 ] demonstrated within- and across-run variability of 4.7% and 4.1%, respectively. Additionally, Picard et al documented a lower LOQ (0.22%) than that reported by the manufacturer ( Table 5 ) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various methods can be employed for chimerism analysis utilizing polymorphic markers to differentiate donor cells from recipient cells. These methods encompass chromosome analysis, fluorescence in situ hybridization (FISH), short tandem repeat (STR) PCR, quantitative PCR (qPCR), digital PCR (dPCR), and next-generation sequencing (NGS) [ 2 , 7 , 8 ]. Each method has its strengths and weaknesses in terms of sensitivity, precision, applicability, and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a paper published by Picard et al [26] using a total of 38 samples, a comparison of chimerism quantification data for two new digital PCR systems and two NGS-based chimerism quantification methods was performed. They found that all three existing NGS kits, Devysr ® (Devyser Chimerism), CareDX (AlloSeq HCT), and GenDx (NGStrack) are similar in terms of analytical performance.…”
Section: Discussionmentioning
confidence: 99%
“…ME evaluation is also challenging when the sample only contains component “A” or “B”, due to limitations in analytic sensitivity [STR sensitivity is around 1%–5% ( Picard et al, 2023 )]. Of note, a small number of laboratories use methods like NGS, real-time PCR or digital PCR, which can reach a limit of detection down to 0.01%–0.1% ( Picard et al, 2023 ).…”
Section: Me: Monitoring Engraftment Proficiency Testingmentioning
confidence: 99%
“…ME evaluation is also challenging when the sample only contains component “A” or “B”, due to limitations in analytic sensitivity [STR sensitivity is around 1%–5% ( Picard et al, 2023 )]. Of note, a small number of laboratories use methods like NGS, real-time PCR or digital PCR, which can reach a limit of detection down to 0.01%–0.1% ( Picard et al, 2023 ). Discrepant results are usually due to wrong interpretation of “stutter” bands, which are PCR errors due to strand slippage during primer extension ( Levinson and Gutman, 1987 ), resulting in 1 less STR.…”
Section: Me: Monitoring Engraftment Proficiency Testingmentioning
confidence: 99%